The role of chromosomal microarray analysis among fetuses with normal karyotype and single system anomaly or nonspecific sonographic findings. (15th October 2020) - Hui, Annie Sy; Chau, Matthew Hoi Kin; Chan, Yiu Man; Cao, Ye; Kwan, Angel Hw; Zhu, Xiaofan; Kwok, Yvonne K.; Chen, Zihan; Lao, Terence T.; Choy, Kwong Wai; Leung, Tak Yeung
Abstract: Introduction: Chromosomal microarray analysis is recommended as the first‐tier test for the evaluation of fetuses with structural anomalies. This study aims to investigate the incremental diagnostic yield of chromosomal microarray over conventional karyotyping analysis in fetuses with anomalies restricted to one anatomic system and those with nonspecific anomalies detected by sonography. Material and methods: This is a retrospective cohort analysis of 749 fetuses undergoing prenatal diagnosis for abnormal ultrasound findings isolated to one anatomic system and normal karyotype, utilizing chromosomal microarray. Overall, 495 (66%) fetuses had anomalies confined to one anatomic system and 254 (34%) had other nonspecific anomalies including increased nuchal translucency (≥3.5 mm), cystic hygroma, intrauterine growth restriction and hydrops fetalis. Results: Fetuses with ultrasound anomalies restricted to one anatomic system had a 3.0% risk of carrying a pathogenic copy number variant; the risk varied dependent on the anatomic system affected. Fetuses with confined anomalies of the cardiac system had the highest diagnostic yield at 4.6%, but there were none in the urogenital system. Fetuses with nonspecific ultrasound anomalies had the highest diagnostic yield in fetuses with an intrauterine growth restriction at 5.9%. Overall, fetuses with a nonspecific ultrasound anomaly were affected with pathogenic copy number variants in 1.6% in the cases. Conclusions: The diagnostic yield of chromosomal microarray in fetuses with normal karyotype and ultrasound abnormality confined to a single anatomic system was highest if it involved cardiac defects or intrauterine growth restriction. This diagnostic yield ranges from 0% to 4.6% depending on the anatomic system involved. Chromosomal microarray has considerable diagnostic value in these pregnancies.